A Challenge to Presidential Wars: Smith v. Obama. Issue 2 (4th May 2017) - Fisher, Louis
ABSTRACT: From World War II to the present time, presidents have exceeded constitutional and statutory authority in exercising the war power. In doing so, they violate the rule of law, the principle of self-government, and the system of checks and balances. The U.S. Constitution expressly rejected the British model that placed with the Executive exclusive authority over external affairs, including taking the country from a state of peace to one of war. The Framers assigned that power solely to Congress. A lawsuit filed in 2016, Smith v. Obama, asked a federal district court to decide whether President Obama may engage in war without receiving express authority from Congress.